REPOSISI DAN PERAN BIROKRASI - Firdaus Fakih; Susi Lawati (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2020)
The position and role of the state apparatus which is often referred to as the government bureaucracy is of concern, because most of the life of the state is regulated and determined by the government through the government bureaucracy. The position and role of the bureaucracy is interesting to discuss because the position and role have not been as expected. In general, the position of the government bureaucracy is always opposite between the rulers of the government / state and the people or the people they control. Where should the position of the bureaucracy be and what role should it play as long as the bureaucracy emphasizes the position of political power rather than socio-culture, the bureaucracy becomes a servant to certain political interests so that services to the public are replaced by services to political power, so that every service is rooted in public service. always has the color of power and prioritizes the political interests served instead of the public interest as a whole. In line with the changes that have occurred in the order of government implementation and the development of community life in various aspects of life, the role of society in the life of the state has begun to be felt. Public demands began to affect the government work bureaucracy system. This situation in turn makes it increasingly possible to change the position and role of the public bureaucracy.